Flavor formation and phospholipids degradation of crayfish meat treated by boiling combined air-frying during accelerated storage - Mingzhu Zhou; Dongyin Liu; Hongyuan Tan; Chao Wang; Wei Yu; Guangquan Xiong; Lan Wang; Wenjin Wu; Yu Qiao (Food Chemistry: X)
Thermal treatment is an essential processing method in crayfish processing. This study analyzed the changes in lipids and volatile compounds in crayfish muscle subjected to three thermal processes: boiling (BO), air-frying (AF), and boiling combined air-frying (BO-AF). Aldehydes and heterocyclic compounds were found to be the predominant volatile compounds in crayfish muscle during thermal processing and storage. The intensity of lipid oxidation (POV, TBARS and p-AnV) was greatest in AF, and was notably lower in BO-AF. the total concentration of free fatty acids (FFAs) was highest in the AF group (4.14 mg/g) after processing, followed by BO (3.26 mg/g) and BO-AF (2.04 mg/g). During storage, the FFAs content gradually decreased, with generally lower levels observed at 65 °C compared to 45 °C. A total of 383 phospholipid species were identified, phosphatidylethanolamine being the primary difference lipid type in BO (26.7 %) and AF (36.7 %), while fatty acids were the main differential lipid types in BO-AF group, under the comparison between processed and stored. Overall, the BO-AF method improved the flavor sensory and decreased lipid oxidation, compared to the other two methods. These findings provide valuable insights into the effects of different thermal processing and storage methods on the quality and safety of crayfish muscle.